BEZ235 Increases the Sensitivity of Hepatocellular Carcinoma to Sorafenib by Inhibiting PI3K/AKT/mTOR and Inducing Autophagy. (20th April 2021) - Cao, Weiya; Liu, Xueke; Zhang, Yinci; Li, Amin; Xie, Yinghai; Zhou, Shuping; Song, Li; Xu, Ruyue; Ma, Yongfang; Cai, Shiyu; Tang, Xiaolong
Abstract : Acquired resistance of hepatocellular carcinoma (HCC) to sorafenib (SFB) is the main reason for the failure of SFB treatment of the cancer. Abnormal activation of the PI3K/AKT/mTOR pathway is important in the acquired resistance of SFB. Therefore, we investigated whether BEZ235 (BEZ) could reverse acquired sorafenib resistance by targeting the PI3K/mTOR pathway. A sorafenib-resistant HCC cell line Huh7 R was established. MTT assay, clone formation assay, flow cytometry, and immunofluorescence were used to analyze the effects of BEZ235 alone or combined with sorafenib on cell proliferation, cell cycle, apoptosis, and autophagy of Huh7 and Huh7 R cells. The antitumor effect was evaluated in animal models of Huh7 R xenografts in vivo . Western blot was used to detect protein levels of the PI3K/AKT/mTOR pathway and related effector molecules. In vitro results showed that the Huh7 R had a stronger proliferation ability and antiapoptosis effect than did Huh7, and sorafenib had no inhibitory effect on Huh7 R . SFB + BEZ inhibited the activation of the PI3K/AKT/mTOR pathway caused by sorafenib. Moreover, SFB + BEZ inhibited the proliferation and cloning ability, blocked the cell cycle in the G0/G1 phase, and promoted apoptosis in the two cell lines. The autophagy level in Huh7 R cells was higher than in Huh7 cells, and BEZ or SFB + BEZ further promoted autophagy in the two cell lines. In vivo, SFB + BEZ inhibited tumor growth by inducing apoptosis and autophagy. We concluded that BEZ235 enhanced the sensitivity of sorafenib through suppressing the PI3K/AKT/mTOR pathway and inducing autophagy. These observations may provide the experimental basis for sorafenib combined with BEZ235 in trial treatment of HCC.